Diagnosis, Phenotype, and Molecular Genetics of Congenital Analbuminemia - Minchiotti, Lorenzo; Caridi, Gianluca; Campagnoli, Monica; Lugani, Francesca; Galliano, Monica; Kragh-Hansen, Ulrich (Frontiers in Genetics, 2019)
Congenital analbuminemia (CAA) is an inherited, autosomal recessive disorder with an incidence of 1:1,000,000 live birth. Affected individuals have a strongly decreased concentration, or complete absence, of serum albumin, a condition which can be readily detected by serum protein electrophoresis. However, due to differential diagnoses, examination of the albumin gene is necessary for establishing the molecular diagnosis of the condition. CAA can lead to serious consequences in the pre- and peri-natal period, it can cause preterm birth and neonatal or early childhood death. By contrast, CAA is better tolerated in adulthood. Clinically, in addition to the low level of albumin, the patients almost always have hyperlipidemia, but they usually also have mild oedema, reduced blood pressure and fatigue. The fairly mild symptoms in adulthood are due to compensatory increment of other plasma proteins. It is uncertain, whether the hyperlipidemia increases the risk for developing atherosclerosis or other diseases. Because of the lack of albumin, albumin-binding drugs should be administered with care. The condition is rare, and only about 90 cases have been detected worldwide. However, molecular analysis of the ALB gene by DNA and mRNA sequencing identified so far 27 different variations; most of them are loss of function (LoF) affecting splicing, nonsense and frameshift/deletions and insertions, but also a variation in the start codon was detected. Most are unique, peculiar for each affected family, but one, a frame-shift deletion called Kayseri, has been found to cause about one third of the known cases allowing to presume a founder effect.